2016
DOI: 10.1007/s11084-016-9524-z
|View full text |Cite
|
Sign up to set email alerts
|

Interaction, at Ambient Temperature and 80 °C, between Minerals and Artificial Seawaters Resembling the Present Ocean Composition and that of 4.0 Billion Years Ago

Abstract: Probably one of the most important roles played by minerals in the origin of life on Earth was to pre-concentrate biomolecules from the prebiotic seas. There are other ways to pre concentrate biomolecules such as wetting/drying cycles and freezing/sublimation. However, adsorption is most important. If the pre-concentration did not occur-because of degradation of the minerals-other roles played by them such as protection against degradation, formation of polymers, or even as primitive cell walls would be seriou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
7
0
2
Order By: Relevance
“…Of course, control experiments (in distilled water) are necessary to provide an idea of the effect of the ions. We observed that this seawater influences the stability of minerals and the adsorption of nucleic acid bases (Anizelli et al ., 2015, 2016; Canhisares-Filho et al ., 2015; Carneiro et al ., 2017; Villafañe-Barajas et al ., 2018; Zaia et al ., 2018). In addition, the interaction of cations of seawater (Ca 2+ , Mg 2+ , Sr 2+ and Na + ) with nucleic acid bases changed their reactivity (Anizelli et al ., 2014; Baú et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, control experiments (in distilled water) are necessary to provide an idea of the effect of the ions. We observed that this seawater influences the stability of minerals and the adsorption of nucleic acid bases (Anizelli et al ., 2015, 2016; Canhisares-Filho et al ., 2015; Carneiro et al ., 2017; Villafañe-Barajas et al ., 2018; Zaia et al ., 2018). In addition, the interaction of cations of seawater (Ca 2+ , Mg 2+ , Sr 2+ and Na + ) with nucleic acid bases changed their reactivity (Anizelli et al ., 2014; Baú et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the work of Izawa et al (2010), who performed an experiment through leaching of meteorite samples in Tagish Lake, Zaia (2012) suggested a model of artificial seawater. For several years our group has been working with this artificial seawater model, which probably better resembles the major ions of the ocean of the prebiotic Earth (Anizelli et al, 2014(Anizelli et al, , 2015(Anizelli et al, , 2016Canhisares-Filho et al, 2015;Carneiro et al, 2017;Villafañe-Barajas et al, 2018;Zaia et al, 2018;Baú et al, 2019). Unlike the seawater in the oceans today that have a high concentration of Na + and Cl − (Bearman, 2004), this artificial seawater contains high concentrations of Mg 2+ and SO 4 2− (Zaia, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Since the Fe 3+ ion is considered a hard acid, the metal coordinates with the SCN − ion through nitrogen to form isothiocyanate complexes (Pearson, 1963). It is well known that goethite is formed when sulphur compounds interact with the Fe 3+ cation Cornell and Schwertmann, 2003;Vu and Moreau, 2015;Carneiro et al, 2013;Samulewski et al, 2020). Therefore, this may be an indication that Fe 3+ interacted with the SCN − ion also by sulphur.…”
Section: Pearson's Theorymentioning
confidence: 99%
“…The authors obtained the following order of cations: Mg 2+ > Ca 2+ >> Na + ≈ K +, and anions: SO 4 2− >> Cl − . In the last few years, we have been using this artificial seawater, 4.0 Gy and the results showed that the ion composition of seawater has an effect on the adsorption of nucleic acid bases as well as on the stability of the minerals (Canhisares-Filho et al ., 2015; Anizelli et al ., 2016 a , b ; Carneiro et al ., 2017; Villafañe-Barajas et al ., 2018; Zaia et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A adsorção desse aminoácido em quartzo e calcita e as implicações para a origem da vida foram avaliadas por Churchill e colaboradores (2004) (CANHISARES-FILHO et al, 2015;CARNEIRO et al, 2017;FARIAS et al, 2016) a outra com uma composição salina quase três vezes maior que a do mar atual e com uma variedade de 10 elementos químicos presentes na formulação foi elaborada para o estudo para observar a contribuição do ambiente nos processos de adsorção.…”
Section: Introductionunclassified